3rd International Orthodontic Conference of ODOAN (Nepal), Nepal Tourism Board, Kathmandu, Sept. 21-22, 2013 (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Abstract not availableBan J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.37-39